Optical quantum normalized electroosmotic Heisenberg magnetical optimistic energy - Korpinar, Talat; Korpinar, Zeliha; Asil, Vedat (Springer, 2023)
In this paper, we construct optical normalization operator of magnetic field by using Levi Civita connection. Then, we obtain optical normalized quasi tangent electroosmotic magnetical optimistic energy according to quasi frame. Finally we design microfluidic optical recursional quasi tangent electroosmotic magnetical optimistic energy.
Keywords: Optical recursion; Optical ferromagnetic microscale; Flexible elastic microscale; Electric optimistic density